Tecnologia supercrítica associada a líquidos iônicos aplicados ao processo de tingimento têxtil - Mazzer, Helen Ronise (2013)
New technologies have been developed or adapted to reduce harm to the environment andreduce the use of organic solvents in the concept of "green chemistry". The search for new processes to reduce the emission of large quantities of effluent produced by the textile industry has made studies would lead to the possibility of combining ionic liquids withsupercritical technology to replace the conventional dyeing processes. However, the technical and economic feasibility for the application of supercritical technology require prior knowledge of the phase behavior of the mixture of compounds involved in the process.The technical feasibility of the economic use of ionic liquids involves processes of synthesis and recovery of ionic liquids after use. It is proposed as a system for dyeing, alternatively, with the association of: ionic liquid / dye, ionic liquid / dye / sc CO2, ionic liquid / dye / water, scCO2 / dye. The ionic liquid employed were: 1-butyl-3-methylimidazole tetrafluoroborate ([bmim] [BF4]), 1-butyl-3-methylimidazole hexafluorophosphate ([bmim] [PF6]), 1-hexyl-3- methylimidazole acetate ([hmim] [OAc]), -octyl-3-methylimidazole acetate ([omim] [OAc]), ethyl hydroxyethyl (2HEAA) and dye employed were: disperse dyes Red 60, Orange 30, Blue 56 and Yellow 163. Thus, this paper proposes to study the phase behavior at high pressures using the synthetic method for the binary systems CO2 dye and dyeing using supercritical technology with ionic liquid and supercritical CO2 (scCO2). It also proposes a methodology for the reuse of dye bath for a new dyeing and recovery of ionic liquids through the dyeing using a charcoal column and dichloromethane as eluent.